Current imaging methods for assessing Graves` orbitopathy activity with particular emphasis on FDG-PET - Ochmann, Anna; Winder, Mateusz; Nalewajka-Kołodziejczak, Joanna; Chudek, Jerzy (Frontiers in Endocrinology, 2023)
The most frequent extrathyroidal Graves' disease manifestation is Graves' orbitopathy (GO). The treatment of GO is determined by its severity and activity. There is currently no reliable, impartial method for assessing it clinically or distinguishing fibrosis from active inflammatory disorders. Today, imaging methods including orbital ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI) are frequently employed to show pathological abnormalities in the ocular adnexa of GO patients. In addition, a not widely accepted technique – 99mTc-DTPA SPECT – has some potential to evaluate retrobulbar inflammation in GO patients. However, FDG-PET/CT is possibly superior to other imaging modalities in detecting inflammation in GO and it may be useful in assessing disease activity in case of clinical or serological uncertainty. It might also act as an early indicator of GO development and its aggravation before irreversible tissue alterations take place and may be used in the differential diagnosis of inflammatory disorders of the orbit. However, before FDG-PET/CT could be applied in daily clinical practice, the methodology of GO activity assessment with defined cut-off values for radionuclide concentration – standardized units of value (SUV) have to be established and validated. In addition, the limitations of this technique have to be recognized.